My sister, the serial killer : a novel - Braithwaite, Oyinkan (New York : Anchor Books, 2019)
Satire meets slasher in this short, darkly funny hand grenade of a novel about a Nigerian woman whose younger sister has a very inconvenient habit of killing her boyfriends. "Femi makes three, you know. Three and they label you a serial killer." Korede is bitter. How could she not be? Her sister, Ayoola, is many things: the favorite child, the beautiful one, possibly sociopathic. And now Ayoola's third boyfriend in a row is dead. Korede's practicality is the sisters' saving grace. She knows the best solutions for cleaning blood, the trunk of her car is big enough for a body, and she keeps Ayoola from posting pictures of her dinner to Instagram when she should be mourning her "missing" boyfriend. Not that she gets any credit. A kind, handsome doctor at the hospital where Korede works is the bright spot in her life. She dreams of the day when he will realize they're perfect for each other. But one day Ayoola shows up to the hospital uninvited and he takes notice. When he asks Korede for Ayoola's phone number, she must reckon with what her sister has become and what she will do about it.
Keywords: Serial murderers -- Fiction; Thrillers (Fiction)